Pendampingan sertifikasi halal umkm produk jamu tradisional di kelurahan wonoasih: Pendampingan sertifikasi halal - M.Fathan Afathoni Z; Himmatul Izzah; Masyrifah Nur; Rodiatul Jennah; Muhammad Nabat Ardli (LPPI UMN AL WASHLIYAH, 2025)
This community service program aims to enhance the knowledge and skills of traditional herbal medicine (jamu) MSME actors in Wonoasih Sub-district, Probolinggo City, regarding the process of obtaining halal certification. Halal certification is an essential instrument to strengthen product competitiveness, increase consumer trust, and support business sustainability based on the principles of halal and thayyib. The method employed was Participatory Action Research (PAR), involving the active participation of participants throughout all stages of the program. The activities included socialization and counseling on the urgency of halal certification, group discussions to identify challenges, technical training on the use of the Halal Information System (SIHALAL), individual assistance in preparing administrative documents, and simulation practices of applying halal standards in herbal medicine production. The results indicate a significant improvement in participants’ understanding of the halal certification procedures, their ability to prepare required documents, and their readiness to implement halal standards in their respective business units. This program demonstrates that a participatory approach effectively encourages MSMEs to be more prepared in fulfilling halal certification requirements while fostering greater awareness of product halalness. Consequently, this program contributes to strengthening the capacity of local MSMEs and supports the development of a halal-based economy at the regional level.